2011
DOI: 10.3171/2011.1.jns101530
|View full text |Cite
|
Sign up to set email alerts
|

Brain injury after intracerebral hemorrhage in spontaneously hypertensive rats

Abstract: Object-Hypertension is the main cause of spontaneous intracerebral hemorrhages (ICH), but the effects of hypertension on ICH-induced brain injury have not been well studied. In this study, we examined ICH-induced brain injury in spontaneously hypertensive rats (SHR).Methods-This two-part study was performed on 12 weeks old male SHR and Wistar Kyoto (WKY) rats. First, rats received an intracaudate injection of 0.3 units collagenase and hematoma sizes were determined at 24 hours. Second, rats were injected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…As another example, BP clearly affects ischemic injury in animal models (Zhu and Auer, 1995) and is thought to affect outcome in ICH patients . There is also some data that higher BP worsens outcome in rodents subjected to an ICH (Wu et al, 2011a), but a complete dose-response effect has not been established, nor it is clear whether this differs among models. We have measured BP following collagenase-induced ICH in normotensive rats (MacLellan et al, 2004).…”
Section: Physiological Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…As another example, BP clearly affects ischemic injury in animal models (Zhu and Auer, 1995) and is thought to affect outcome in ICH patients . There is also some data that higher BP worsens outcome in rodents subjected to an ICH (Wu et al, 2011a), but a complete dose-response effect has not been established, nor it is clear whether this differs among models. We have measured BP following collagenase-induced ICH in normotensive rats (MacLellan et al, 2004).…”
Section: Physiological Variablesmentioning
confidence: 99%
“…As in the ischemia field, it makes sense to test putative neuroprotectants in aged animals. Similarly, the use of other comorbidities, such as hypertensive animals (Wu et al, 2011a), is warranted. Preexisting hypertension is obviously an important consideration in ICH studies, but the impact of post-ICH alterations in BP must also be considered.…”
Section: Impact Of Comorbidities and Gendermentioning
confidence: 99%
“…In rat models of intracerebral hemorrhage (78)(79)(80) have been demonstrated the mentioned physiopathological events, and higher size of hemorrhage in the hyperglycemic rat groups. In a recent experiment was observed that in response to the intracerebral hemorrhage lesion, significant increase of albumin was ubiquitously observed in the brains of normoglycemic rats but not in the brains of hyperglycemic rats.…”
Section: Hyperglycemia and The Sichmentioning
confidence: 92%
“…The early activation of microglia in the peri-ICH area (Rosidi et al 2011;Wagner et al 2005;Wagner 2007) is linked with extracellular serine-proteases (Wagner et al 2003;Wang and Doré 2007;Xue and Yong 2008) and observed in brain of SHRs at ICH (Wu et al 2011). Thrombin -one of such blood-derived proteases involved in mechanisms of brain injury after ICH and modification of its level may coordinate the components of the endogenous response Keep et al 2011;Badu et al 2012).…”
Section: Synaptic Responses In Slices During Perfusion With Autologoumentioning
confidence: 99%